Estudos físico-químicos do sistema Na | Na-β/βʺ-Al2O3 | NaAlCl4 | Al de uma bateria Na-Al - Grespan, Giovani Luiz (2024)
PHYSICAL-CHEMICAL STUDIES OF THE SYSTEM Na | Na-β/βʺ-Al2O3 | NaAlCl4 | Al OF A Na-Al BATTERY. The objective of this work was to understand the kinectics of the charge transfer processes at the interface Na | Na-β/βʺ-Al2O3. For this, a complete investigation of the system was necessary, from the manufacture of specific experimental devices for this type of battery, the production and characterization of the fused salt of sodium tetrachloride (NaAlCl4) and the solid electrolyte of Na-β/βʺ-alumina until the understanding of the electrochemical processes that occur at the interfaces of the system: Na(f) | Na-β/βʺ-alumina(s) | NaAlCl4(f) | Al. For the investigations, U-shaped electrochemical cells and specific ovens were designed and developed to operate at temperatures between 160 and 320 °C inside a dry box. The NaAlCl4 salt was synthesized in the laboratory from the sublimation of AlCl3 followed by reaction with NaCl at 185 °C, obtaining a yield of 92 %. The NaAlCl4 salt was also obtained from the oxidation of an Al electrode in an electrochemical cell. Both salts were characterized by melting point, X-ray diffratometry and Raman spectroscopy. Voltammetric studies of an Al working electrode in molten NaAlCl4 at 250 °C were carried out, using an Al(s)/AlCl4–(f) reference electrode. Processes associated with the reversible half-reaction Al(s) + 4Cl–(f) ↔ AlCl4–(f) + 3e– and also the half-reaction at 300 mV more positive potentials Al(s) + 7AlCl4–(f) ↔ 4Al2Cl7–(f) + 3e– were observed. Flat solid disks of Na-β/βʺ-alumina(s) were prepared and characterized at different temperatures by electrochemical impedance spectroscopy (EIS). These discs prepared presented ~80% of the Na-βʺ-alumina phase with an ionic conductivity of 1.7 x 10–2 Ω–1 cm–1 for Na+ ions at 300 °C. The Arrhenius plot obtained for these discs showed a change in slope, indicating a change in the transport mechanism of Na+ ions above and below 188 °C, with values of activation energies, Ea of 0.39 and 0.67 eV, respectively. The Na-β/βʺ-alumina(s) discs showed a porosity of ~19 % due to some problems observed in the sintering process. To improve the wettability of Na(f) on the surface of Na-β/βʺ-alumina(s), a porous carbon black conductive paint with additives was developed. This paint was applied on the surface of Na-β/βʺ-alumina(s) with aid of an airbrush, in order to obtain good adhesion. Analysis by scanning electron microscopy (SEM) demonstrated topological and compositional homogeneity beyond a thickness of ~50 μm. Using the sodium sessile drop method at 250 °C, contact angles of Na(f) on the surfaces of Na-β/βʺ-alumina without and with the paint coating were determined, obtaining 145° and 38°, respectively. These results demonstrate the good wettability caused by the carbon black-based coating. Finally, studies of the redox processes at the Na(f) | Na-β/βʺ-alumina interface were carried out using galvanostatic and voltammetric measurements. The obtained results showed an ohmic behavior due to the resistivity of Na-β/βʺ-alumina. EIS measurements carried out at open circuit potential and between 160 and 320 °C for the interface Na(f) | Na-β/βʺ-alumina allowed determining the values of charge-transfer resistance and activation energy at this interface, resulting in 1.37 Ω cm–2 (at 250 °C) and 0.11 eV, respectively. From these results, it was possible to understand the resistive contribution of each interface during the charging and discharging processes of the cell Na(f) | Na-β/βʺ-alumina(s) | NaAlCl4(f) | Al.